2012
DOI: 10.2174/092986612803217006
|View full text |Cite
|
Sign up to set email alerts
|

Novel Design of Short Antimicrobial Peptides Derived from the Bactericidal Domain of Avian β-defensin-4

Abstract: Short antimicrobial peptides were designed and synthesized by C-terminal truncation and residue substitution of avian β-defensin-4. The biological activity of these peptides was examined to elucidate the quantitative structure-activity relationships and find a lead peptide for the development of a novel antimicrobial peptide. The results showed that the truncation of the avian β-defensin-4 eliminated the hemolysis of the peptide. The GLI13 derivative, developed by substituting the Cys of the truncated peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Increased cationicity also helps to enhance antibacterial activity [ 9 ]. Cationicity is important for killing bacteria [ 47 ], but simply increasing the net charge does not result in the improvement of antimicrobial potency [ 48 ]. Hydrophobicity also requires an optimal range to enhance antibacterial activity [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased cationicity also helps to enhance antibacterial activity [ 9 ]. Cationicity is important for killing bacteria [ 47 ], but simply increasing the net charge does not result in the improvement of antimicrobial potency [ 48 ]. Hydrophobicity also requires an optimal range to enhance antibacterial activity [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Paulsen et al reported that the N-terminal fragment arasin 1(1–23) was almost equally active to the full length peptide arasin 1(a 37-residue peptide) [14]. We have previously shown that the truncation of the C-terminal region of linear chicken-defensin-4 (AvBD-4) retained the antimicrobial activity and eliminated its hemolytic activity [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that the GLI13-8 peptide derived from the linear AvBD-4 (RL38) exerted antimicrobial activities against Gram-positive and Gram-negative bacteria and showed a low hemolytic activity towards human erythrocytes [21]. In this study, it was shown that the peptide GLI13-8 rapidly initiated cytotoxicity and significantly inhibited the viability of three tumor cell lines, especially HepG2 cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies reported that most AMPs, including magainin II and defensins, induced pore formation in cellular membranes [22,25,32]. We previously reported that GLI13-8 contained high net positive charges [21]. The positive charges interact electrostatically with the negative charges on the cancer cell surface and the amphipathicity favors the peptide to insert into the membrane.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation